A Case of Hemophagocytic Lymphohistiocytosis and Kawasaki Disease: Concurrent or Overlapping Diagnoses?. Issue 1 (January 2018) - Bechtel, Allison S.; Joyce, Michael
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is not always suspected at the time of presentation. It is often mistaken for other diagnoses; complicated by the fact that it is often associated with an inciting event that has significant overlap. Kawasaki disease, along with other disorders, such as Ebstein Barr Virus infection, are conditions that may lead HLH. Our patient had a presentation that was consistent with Kawasaki disease on initial presentation, however subsequently met the diagnostic criteria of HLH. It provided an interesting discussion about diagnoses with clinical criteria and how the overlap can sometimes delay or complicate initial diagnosis.